Lekki Deepsea Port Its Prospect, Challenges and Its Impact to Nigerian Economy - Abeku A.N.; Egelu F.D.; Ogola D.B.; Ifegha, D.O.; Okpara R.A. (International Journal of Maritime and Interdisciplinary Research, 2024)
This study examined Lekki Deepsea port its prospect, challenges and its impact to Nigerian Economy. The researcher employed the descriptive survey research design. A total of 75 responses were validated from the survey. From the responses obtained and analysed, the findings revealed that there are significant prospects for the development of Lekki deep seaport and its impact to Nigeria economy. Lekki Deepsea port will positively impact on trade and commerce, there by facilitating the import and export of goods and improving the efficiency of trade. Also enhancing Nigeria's overall competitiveness and boosts economic growth to a very high extent. The findings also shed light on the intricate relationship betweenLekki Deepsea port development and economic development. Therefore, this study recommends that government and management of Nigeria Port Authority are to ensure sustainable and inclusive development alongside the expansion of deep-sea ports. Regulatory mechanisms and environmental safeguards should be in place to mitigate negative impacts such as pollution, displacement, and congestion. Efforts should be made by the government and management of Nigeria Port Authority to address logistic bottlenecks and improve ease of doing business to fully realize the prospects of Lekki deep-sea ports for the Nigerian economy
This study examined Lekki Deepsea port its prospect, challenges and its impact to Nigerian Economy. Regulatory mechanisms and environmental Safety measures should be in place to mitigate negative impacts such as pollution, displacement, and congestion.
Keywords: Deep seaport; Prospect; Lekki; Challenges; Job creation.